Subcutaneous defibrillator use with unipolar pacemakers: Cautiously possible - Matanyahu Rubinstein; Angela Zhu; Justin A. Mariani; Hitesh C. Patel (Indian Pacing and Electrophysiology Journal, 2023)
Implantation of subcutaneous implantable cardioverter-defibrillator in a patient with existing unipolar pacemaker is against manufacturer recommendations. We report the case of a successful subcutaneous implantable cardioverter-defibrillator implantation in a patient with Fontan circulation and concomitant active unipolar pacing and present a summary of recommendations when considering subcutaneous implantable cardioverter-defibrillator implantation with unipolar pacing. Recommendations included: pre-procedure screening, rescreening during implantation and ventricular fibrillation induction, pacemaker programming, and post-procedure investigations.